Improvement of Learning and Memory Induced by Cordyceps Polypeptide Treatment and the Underlying Mechanism. (15th March 2018) - Yuan, Guangxin; An, Liping; Sun, Yunpeng; Xu, Guangyu; Du, Peige
Abstract : Our previous research revealed that Cordyceps militaris can improve the learning and memory, and although the main active ingredient should be its polypeptide complexes, the underlying mechanism of its activity remains poorly understood. In this study, we explored the mechanisms by which Cordyceps militaris improves learning and memory in a mouse model. Mice were given scopolamine hydrobromide intraperitoneally to establish a mouse model of learning and memory impairment. The effects of Cordyceps polypeptide in this model were tested using the Morris water maze test; serum superoxide dismutase activity; serum malondialdehyde levels; activities of acetyl cholinesterase, Na+-k+-ATPase, and nitric oxide synthase; and gamma aminobutyric acid and glutamate contents in brain tissue. Moreover, differentially expressed genes and the related cellular signaling pathways were screened using an mRNA expression profile chip. The results showed that the genes Pik3r5, Il-1 β, and Slc18a2 were involved in the effects of Cordyceps polypeptide on the nervous system of these mice. Our findings suggest that Cordyceps polypeptide may improve learning and memory in the scopolamine-induced mouse model of learning and memory impairment by scavenging oxygen free radicals, preventing oxidative damage, and protecting the nervous system.